ANALISIS DAMPAK SOSIAL DAN EKONOMI PADA PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS SUMBER DAYA - Reiki Nauli Harahap (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to analyze the social and economic impact of resource-based community empowerment programs. The program, which was initiated by a company in Kalimantan, utilizes and develops the potential of weaving as local wisdom through corporate social responsibility activities. The social and economic impact is manifested in the form of community satisfaction as beneficiaries of the program. Community satisfaction is assumed to be the success of the program and providing social and economic impact to the beneficiaries. This research uses quantitative methods. Data was collected by interviewing the overall beneficiaries of the program, a total of 23 people. Data collection using purposive sampling techniques. The data analysis technique uses a simple average value by comparing the weighted value and the weighted value so that a percentage of the satisfaction value is obtained. The next analysis technique is servqual analysis, which is to compare the value of expectations and the value of reality of criteria. The results showed that beneficiaries felt the social and economic impact of the resource-based community empowerment program with a value of 4.90 or 97.95%. This research is only able to analyze simple social and economic impacts, it is necessary to measure the impact with other methods as a comparison, namely by using social return on investment (SROI).